1998
DOI: 10.1055/s-2007-1016249
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Factors as Markers and Mediators of Endothelial Cell Dysfunction in Preeclampsia

Abstract: During the past decade a new hypothesis has been formulated that explains many of the disparate findings associated with the pregnancy syndrome preeclampsia. With an increased awareness of the physiological significance of vascular endothelial cell function, the seemingly unrelated signs of hypertension, proteinuria, edema, and hypercoagulability have converged to provide clinical evidence of a unifying pathophysiological mechanism: systemic, maternal endothelial cell dysfunction. Investigators have attempted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(63 citation statements)
references
References 122 publications
1
61
0
1
Order By: Relevance
“…11,12,17,[23][24][25][26][27][28][29][30][31][32][33] Because NO is an important physiological vasodilator in normal pregnancy, it follows that NO deficiency during preeclampsia has been implicated in the disease process. 18,[23][24][25][26][27][28][29][30][31][32][33] Although numerous studies indicate chronic NOS inhibition in pregnant rats produces hypertension associated with peripheral and renal vasoconstriction, proteinuria, intrauterine growth restriction, and increased fetal morbidity, 11,12,25 it is unclear whether an NO deficiency occurs in women with preeclampsia. Much of the uncertainty in this area of research originates from the difficulty in directly assessing the activity of the NO system in the clinical setting.…”
Section: Potential Mediators Of Endothelial Dysfunction Nitric Oxidementioning
confidence: 99%
See 1 more Smart Citation
“…11,12,17,[23][24][25][26][27][28][29][30][31][32][33] Because NO is an important physiological vasodilator in normal pregnancy, it follows that NO deficiency during preeclampsia has been implicated in the disease process. 18,[23][24][25][26][27][28][29][30][31][32][33] Although numerous studies indicate chronic NOS inhibition in pregnant rats produces hypertension associated with peripheral and renal vasoconstriction, proteinuria, intrauterine growth restriction, and increased fetal morbidity, 11,12,25 it is unclear whether an NO deficiency occurs in women with preeclampsia. Much of the uncertainty in this area of research originates from the difficulty in directly assessing the activity of the NO system in the clinical setting.…”
Section: Potential Mediators Of Endothelial Dysfunction Nitric Oxidementioning
confidence: 99%
“…Although some studies have reported no significant changes in circulating levels of ET-1 during moderate forms of preeclampsia, a possible role for ET-1 as a paracrine or autocrine agent in preeclampsia remains worthy of consideration. 11,12,23,46,47 Because ET-1 is released toward the vascular smooth muscle in a paracrine fashion, changes in plasma levels of ET may not reflect its local production. Indeed, this is one of the reasons why it has been difficult to ascertain whether preeclampsia is associated with altered ET production.…”
Section: Endothelinmentioning
confidence: 99%
“…fibronectin, Von Willebrand factor, endothelin 1, asymmetric dimethyl arginine etc.) to show that endothelial function is impaired in peeclampsia (56). Reduced FMD in second trimester has also been reported to be associated with increased risk of preeclampsia (57).…”
Section: Preeclampsia and Maternal Healthmentioning
confidence: 95%
“…In detail, preeclampsia is a multifactorial disease process that most likely involves immune components, inflammation, genetics, cytokines or vascular factors, and contributes significantly to maternal and perinatal morbidity and mortality (Torry et al, 2004). Its aetiology is still unclear, but its manifestation in mid-gestation is regarded as a disorder of early placentation and culminates in generalized maternal endothelial cell dysfunction that is characteric for preeclampsia (Taylor et al, 1998;Roberts, 1998).…”
Section: Preeclampsiamentioning
confidence: 99%